2021
DOI: 10.3389/fnmol.2021.750578
|View full text |Cite
|
Sign up to set email alerts
|

Fas Apoptosis Inhibitory Molecule Blocks and Dissolves Pathological Amyloid-β Species

Abstract: A number of neurodegenerative diseases are associated with the accumulation of misfolded proteins, including Alzheimer’s disease (AD). In AD, misfolded proteins such as tau and amyloid-β (Aβ) form pathological insoluble deposits. It is hypothesized that molecules capable of dissolving such protein aggregates might reverse disease progression and improve the lives of afflicted AD patients. Here we report new functions of the highly conserved mammalian protein, Fas Apoptosis Inhibitory Molecule (FAIM). We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…We previously showed that FAIM protein possesses heat shock protein (HSP)-like chaperone activity given that FAIM prevents amyloid-β and SOD1 aggregation in an in vitro cell-free system [ 3 , 4 ]. Some HSPs respond to stress conditions by upregulating their expression [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously showed that FAIM protein possesses heat shock protein (HSP)-like chaperone activity given that FAIM prevents amyloid-β and SOD1 aggregation in an in vitro cell-free system [ 3 , 4 ]. Some HSPs respond to stress conditions by upregulating their expression [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…FAIM-S and sHSPs are known to inhibit β-amyloid fibrillization/aggregation in vitro [ 4 , 15 , 16 ]. To examine whether FAIM-S and HSP27 have an additive effect on the prevention of aggregation, we utilized the in vitro β-amyloid fibrillization/aggregation model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations